Table of Content - - (Journal of Educational and Psychological Sciences, 2025)
Table of Content: • The Reality of Interdisciplinary Postgraduate Programs at Tabuk University, Their Challenges, and Requirements for Activating them from the Perspective of Academic Leaders Ms. Marzooqah Abdullah Al-Onizy ,Prof. Abdullah Abdulaziz Al-Sharif • The role of artificial intelligence applications in promoting green education for students of Saudi universities (Islamic, Taiba Tabuk) and the obstacles to their use from their own point of view Dr. Asma Hamed Al-Balawi, Prof. Areej Hamza El-Sisi • The Impact of the "One Million Plastic Caps" Project on Developing Environmental Awareness among Students at the Volunteer Summer Center in the Sultanate of Oman Dr. Huda Ali Alhosni, Ms. Amal Rabee Alkahali, Ms. Zahra Saif Alshkaili , Dr. Moza Ali AlSheyadi • The Impact of Parental styles of socialization on Social Interactions of Male and Female Children in Primary Grades Ms. Manar Ali Al-Asmari ,Co-Prof. Randa Mohammed El-Maghraby, Asst-Prof. Huda Fuad Bajamal • Psychological stress and its relationship with metacognitive thinking during blended learning among a sample of graduate students in educational studies at King Abdulaziz University in Jeddah Ms. Maryam Saad Bashir Al-Rehaili,Ms. Eman Mohammed Yahya Al-Amir,Dr. Manal Yahya Baamer • The Level of Knowledge of Early Childhood Department Student on Psychological Support Methods for Post-Traumatic Stress Disorder in Children Ms. Hajar Abdullah Alqout ,Co-Prof. Gadah Saleh Alsedrani • Analyzing the Reality of Professional Quality of Life and Its Impact on Job Stability among Kindergarten Teachers in Private Schools Ms. Nada Khamis Al-Zahrani